Automatic Identification System (AIS) Based Monitoring System and Its Role in Improving Maritime Transportation Safety in Indonesia - Tri Iriani Eka Wahyuni; Sidrotul Muntaha; Amiruddin Amiruddin; Irwan Jaya; Andi Hasmawati (Politeknik Siber Cerdika Internasional, 2026)
Background: Maritime transportation safety in Indonesia still faces various challenges, marked by a high number of ship accidents and a less-than-optimal vessel traffic monitoring system. The Automatic Identification System (AIS), as a modern navigation technology, has been mandated by the government to improve shipping safety. Objective: This study aims to analyze the effectiveness of the AIS-based monitoring system in improving maritime transportation safety in Indonesia and to identify obstacles in its implementation. Methods: The research used a mixed-methods approach through observations at VTS Makassar, interviews with ship operators and regulators, and distribution of questionnaires to shipping actors. Results: The results showed that AIS plays an important role in increasing navigational awareness, supporting real-time ship traffic monitoring, and aiding search and rescue processes. However, its effectiveness is not yet optimal due to devices being inactive or unfit for use, limited human resource competence, signal interference, and weak regulatory supervision. Conclusion: In conclusion, the AIS system is functionally effective in improving maritime transportation safety but requires regulatory strengthening, improved technical training, and infrastructure updates to ensure its implementation is optimal and sustainable.